Prediction of Depression Scores From Aerobic Fitness, Body Fatness, Physical Activity, and Vagal Indices in Non-exercising, Female Workers - Tonello, Laís; Oliveira-Silva, Iransé; Medeiros, André Ricarte; Donato, Arthur Ney Alves; Schuch, Felipe Barreto; Donath, Lars; Boullosa, Daniel (Frontiers in Psychiatry, 2019)
Background: Depression is associated with a decreased cardiorespiratory fitness, and physical activity [PA] levels, higher rates of obesity, and dysfunction in autonomic control of heart rate [HR]. However, these parameters were mostly recorded with indirect methods. Thus, the aim of the current study was to investigate the relationships between depression scores and objective measures of body fatness, autonomic indices (i.e. HRV and HRR), cardiorespiratory fitness and PA levels; and subsequently to present the best predictive models of depression scores for this population, based on these variables. Methods: Thirty-five non-exercising women (26-43 years; maximal oxygen consumption [VO2max] ~ 17.4 - 38.3 mL/kg/min) volunteered for participation in this study. All participants responded to the Beck Depression Inventory [DBI] and were evaluated for body mass index [BMI], percentage of body fat, sum of skinfolds, and VO2max. Subsequently, over four consecutive days, an orthostatic test and a submaximal exercise on a cycle ergometer were performed to record HRV and HRR, respectively. In addition, incidental PA was recorded during 5 consecutive days using accelerometers. Results: depression scores were related to VO2max (r = -0.446, p = 0.007) and the sum of skinfolds (r= 0.434, p=0.009). Several stepwise multiple linear regression models were performed and only VO2max was revealed as an independent predictor of the Beck scores (ß=-0.446, R²=0.199, p=0.007). Conclusion: The present study revealed that VO2max and the sum of skinfolds were moderately related to depression scores, while VO2max was the only independent predictor of depression scores in female workers.